Maximum joint torque dependency of the crawl swimming with optimized arm stroke - Nakashima, M.; Ono, A. (Journal of Biomechanical Science and Engineering, 2014)
The objectives of this study were to solve computationally the arm stroke in the crawl swimming which maximized the swimming speed for different maximum joint torque conditions, and to investigate the maximum joint torque dependency of the crawl swimming with the optimized arm stroke. In the optimizing calculation, the swimming human simulation model, SWUM, was used for the simulation of the crawl swimming. The maximum joint torque characteristics, which were constructed in the previous study, were imposed as the constraint condition. In order to investigate the maximum joint torque dependency of the optimized arm stroke, four levels of maximum joint torque were prepared. The following findings were obtained from the results of optimization: The maximum swimming speed was realized by shortening the stroke cycle as much as possible although this shortening brought a lower propulsive efficiency as well as a lower stroke length. In a constant maximum joint torque condition, the swimmer does not push the water by turning the palm to the side in the latter half of the underwater stroke at the stroke cycle which brings the maximum swimming speed. The locus of the hand was relatively straight. At the slightly longer stroke cycle, the swimmer pushed the water until the end of the underwater stroke. The locus of the hand was still relatively straight. At the sufficiently longer stroke cycle, the swimmer also pushed the water until the end of the underwater stroke. The locus of the hand, however, became more curved and therefore became a so-called `S-shaped` stroke.